Arah Kebijakan Sektor Pertanian di Indonesia untuk Menghadapi Era Revolusi Industri 4.0 - Ikhsani, Ismi Imania Imania; Tasya, Feninda Eka; Sihidi, Iradhad Taqwa; Roziqin, Ali; Romadhan, Ach Apriyanto (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2020)
Agricultural policy is a government effort in regulating, controlling aspects of development in the agricultural sector with the aim of maintaining and increasing food yields. The great results of the objectives of agricultural policies will be able to be realized if they can be translated into concrete steps and can be implemented consistently in the field. Agricultural policy directions try to see the concept of policies developed and practices to realize the goals of agricultural policies in Indonesia. This study focuses on institutions, regulations and issues of inadequate budget allocation, human resources that are less qualified in the management of land and agricultural products. The purpose of this study is to describe the direction of Indonesian agricultural policy in facing the Industrial Revolution Era 4.0. This research uses qualitative research with a literature review approach. The results showed that there was no synchronization of agricultural policies at various levels of government, low budgets for agricultural development, spatial production practices at the expense of agricultural land in boosting regional income and the low utilization of technology and diversification in the use of agricultural technology showed that agricultural conditions in Indonesia were at an alarming level. Therefore, it is necessary to immediately synchronize agricultural policies at various levels of government and the allocation policies for agricultural development funds.